2013
DOI: 10.11648/j.sjph.20130101.11
|View full text |Cite
|
Sign up to set email alerts
|

Health Hazards and the Socioeconomic Status of Female Labour of Tobacco Processing Mills in Kushtia, Bangladesh

Abstract: This cross sectional study was conducted to identify prevalence of different disease symptoms, nutritional and socioeconomic status in women workers working in tobacco processing plants. The survey was done on a sample of 240 (Two hundred and forty) female tobacco workers. The study was done by direct participatory observation method. The target persons were interviewed on the basis of prepared questionnaires to trace out the research findings. They were physically observed and their anthropometric measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…This finding is in accord with those of Zago et al, 2016 study that assessed the high incidence of non-fatal work-related events in tobacco farmers, [9] and a Ali et al, 2021 study that showed that 90% of tobacco workers think that the work in tobacco production and processing carries significant health hazards [10]. A study of Khatun et al, 2013 in Koshtia, Bangladesh, showed that more than half of the workers have respiratory symptoms, the majority of them suffer from general physical weakness, about two-thirds have muscle pain in the limbs, especially the hands and feet, and more than half have poor nutritional and social status [11].…”
Section: Discussionsupporting
confidence: 85%
“…This finding is in accord with those of Zago et al, 2016 study that assessed the high incidence of non-fatal work-related events in tobacco farmers, [9] and a Ali et al, 2021 study that showed that 90% of tobacco workers think that the work in tobacco production and processing carries significant health hazards [10]. A study of Khatun et al, 2013 in Koshtia, Bangladesh, showed that more than half of the workers have respiratory symptoms, the majority of them suffer from general physical weakness, about two-thirds have muscle pain in the limbs, especially the hands and feet, and more than half have poor nutritional and social status [11].…”
Section: Discussionsupporting
confidence: 85%
“…In this study, majority of the study population i.e., 264 (31.1%) belonged to 25-34 years, which is in accordance to the study conducted by Bansal and Veeresha, 1 and Khatun et al . 7 in which majority of the workers i.e., 592 (42.8%) belonged to 25-34 years of age group.…”
Section: Discussionmentioning
confidence: 97%